Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, dan Kepemilikan Institusional terhadap Nilai Perusahaan - Diah Puspita Sari; Erna Sulistyowati (Ekonomis: Journal of Economics and Business, 2023)
This study focuses on the effect of profitability, liquidity, firm size, and institutional ownership on firm value. Aims to see the effect of profitability, liquidity, firm size, and institutional ownership on firm value. Using a purposive sampling technique using certain criteria, 11 companies were obtained from 26 food and beverage sub-industry companies listed on the Indonesia Stock Exchange in 2016-2020. The results of this study indicate that profitability partially does not affect firm value, liquidity partially affects firm value, firm size partially does not affect firm value, institutional ownership partially affects firm value.